Cholestatic Hepatitis and Thrombocytosis in a Secondary Syphilis Patient - Kim, Gi Hyun; Kim, Byeong Uk; Lee, Ju Hee; Choi, Yong Heok; Chae, Hee Bok; Park, Seon Mee; Youn, Sei Jin; Lee, Ji Yeoun; Yoon, Tae Young; Sung, Rohyun (Journal of Korean medical science, 2010)
The incidence of acute hepatitis in syphilis patient is rare. First of all, our patient presented with hepatitis comorbid with thrombocytosis. To our knowledge, this is only the second report of syphilitic hepatitis with thrombocytosis. The 42-yr-old male complained of flu-like symptoms and skin eruptions on his palms and soles. Laboratory findings suggested an acute hepatitis and thrombocytosis. Serologic test results were positive for VDRL. He recovered from his symptoms and elevated liver related enzymes with treatment. Because syphilitic hepatitis can present without any typical signs of accompanying syphilis, syphilis should be considered as a possible cause in acute hepatitis patients.